ANALISIS BENTUK PARTISIPASI ORANG TUA DAN MASYARAKAT DI SEKOLAH DASAR ISLAM TERPADU - Fadriana, Indra; Indrawati, Sri; Mahardi, Hendri; Erlisnawati, Erlisnawati; Mustafa, M. Nur (Universitas Riau, 2024)
Parental and community participation is one of the most important factors in creating a conducive learning environment and can enhance the effectiveness of student learning in elementary schools. The purpose of this research is to analyze the forms of participation from parents and the community at the Integrated Islamic Elementary School. The method in this study uses a qualitative approach with data collection techniques including observation, interviews, and documentation. This study shows the results of parental participation, namely collaboration with the school, support for the curriculum, the application of values at home, participation in activities outside the classroom, and open communication. Meanwhile, forms of community participation include involvement in decision-making, contributions of time and effort, financial support, participation and evaluation, as well as engagement in extracurricular activities. Challenges such as busy parents and lack of information about school activities can hinder participation. Therefore, schools need to improve communication with the community through social media and counseling programs to raise awareness of the importance of parental involvement.